Intermediate-dose TBI/fludarabine conditioning for allogeneic hematopoietic cell transplantation in patients with peripheral T-cell lymphoma - Krämer, Isabelle; König, Laila; Luft, Thomas; Hegenbart, Ute; Schönland, Stefan; Eichkorn, Tanja; Stadtherr, Peter; Selberg, Lorenz; Müller-Tidow, Carsten; Dreger, Peter (Bone marrow transplantation, 2025)
Allogeneic hematopoietic cell transplantation (alloHCT) is an effective treatment for patients with relapsed/refractory peripheral T-cell lymphoma (PTCL), but the contribution of the conditioning regimen is still unclear. Here we present a retrospective single-center study using conditioning with intermediate-dose total body irradiation (TBI) and fludarabine for alloHCT in PTCL. Forty-seven patients underwent alloHCT for PTCL between 2010 and 2023 after conditioning with fludarabine and intermediate-dose TBI (8 Gy in 87% of the cases). In most patients alloHCT was administered as part of second-line therapy, in 22 (47%) patients after having been primary refractory, and 21 (45%) of the patients were chemoresistant at alloHCT. With a median follow-up of 5.5 years, 5-year progression-free survival (PFS), overall survival, relapse incidence, and non-relapse mortality were 61%, 65%, 24%, and 15%, respectively. The 5-year PFS of patients transplanted with stable disease and progressive disease was 57% and 26%, respectively. Of 11 relapses, only 2 (18%) occurred beyond 6 months post transplant, and no relapse was observed after onset of chronic graft-versus-host disease. AlloHCT with intermediate-dose TBI/fludarabine conditioning is associated with a favorable toxicity/efficacy profile and can provide durable survival in a substantial fraction of patients with PTCL including those with poorly controlled disease at transplant.